2006
DOI: 10.1002/jso.20548
|View full text |Cite
|
Sign up to set email alerts
|

New method for prevention of bile leakage after hepatic resection

Abstract: The combination of fibrin glue and bioabsorbable PGA felt was extremely favorable for prevention of bile leakage after hepatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 22 publications
0
53
0
4
Order By: Relevance
“…Hayashibe at al. [30] analyzed 88 patients after liver resection without biliary reconstruction. The first group of 37 patients with fibrin glue on the resection surface showed biliary leakage in 8.1%, and the second group of 51 patients in whom fibrin glue was combined with bioabsorbable polyglycolic acid sheet showed no postoperative biliary leakage at all (p = 0.003).…”
Section: Biliostatic Efficacy Of Topical Hemostatic Agentsmentioning
confidence: 99%
“…Hayashibe at al. [30] analyzed 88 patients after liver resection without biliary reconstruction. The first group of 37 patients with fibrin glue on the resection surface showed biliary leakage in 8.1%, and the second group of 51 patients in whom fibrin glue was combined with bioabsorbable polyglycolic acid sheet showed no postoperative biliary leakage at all (p = 0.003).…”
Section: Biliostatic Efficacy Of Topical Hemostatic Agentsmentioning
confidence: 99%
“…The author concluded that the used sealant was effective in decreasing the incidence of bile leakage from 56% in the control group to 11% in the sealant group. Hayashibe et al [36] published the results of a retrospective analysis of 88 patients in which they compared the use of fibrin glue in combination with bioabsorbable polyglycol acid (PGA) felt versus fibrin glue alone. They conclude again that sealing with fibrin glue and PGA felt is extremely favorable in the prevention of bile leakage.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…7 The timely detection and repair of intraoperative bile leakage is extremely important, but small leakage points are often difficult to detect. 7 There are several methods for detecting and/or preventing bile leakage after hepatectomy, including bile leakage tests, 1,8,[12][13][14][15] which detect open bile duct stumps on the resection surface by increasing fluid pressure within the duct. 1,8,12 The fluid used can be saline, which is low cost, nontoxic, has low viscosity (allowing the detection of small leakage points) and can be repeated as many times as needed.…”
Section: Introductionmentioning
confidence: 99%
“…1,8,12 The fluid used can be saline, which is low cost, nontoxic, has low viscosity (allowing the detection of small leakage points) and can be repeated as many times as needed. Saline is difficult to detect, however, because it is colourless, [13][14][15] and its use may not lower the incidence of postoperative bile leakage. 13 This can be overcome by the use of a fluorescent dye, but this requires special equipment and there is a risk of allergic reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation